2015
DOI: 10.1088/1367-2630/17/12/123025
|View full text |Cite
|
Sign up to set email alerts
|

Optimal excitation conditions for indistinguishable photons from quantum dots

Abstract: Keywords: quantum dots, quantum description of interaction of light and matter, related experiments, photoluminescence of III-V semiconductors AbstractIn this paper, we present a detailed, all optical study of the influence of different excitation schemes on the indistinguishability of single photons from a single InAs quantum dot. For this study, we measure the Hong-Ou-Mandel interference of consecutive photons from the spontaneous emission of an InAs quantum dot state under various excitation schemes and dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 43 publications
(103 reference statements)
3
50
0
Order By: Relevance
“…14 Rather than the pure dephasing at this temperature, we attribute the dominant dephasing mechanism in our system to timing jitter in the dot emission as a result of above-band excitation. 40 Despite this dephasing, the post-selected visibility at zero time delay should still attain unity in the ideal case, but in practice our measured visibility is limited by the finite time resolution of the detectors which is on the same order as the dephasing time, as well as background emission caused by the heating laser. In summary, we demonstrated two-photon interference from independent cavity-coupled dots on the same chip.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…14 Rather than the pure dephasing at this temperature, we attribute the dominant dephasing mechanism in our system to timing jitter in the dot emission as a result of above-band excitation. 40 Despite this dephasing, the post-selected visibility at zero time delay should still attain unity in the ideal case, but in practice our measured visibility is limited by the finite time resolution of the detectors which is on the same order as the dephasing time, as well as background emission caused by the heating laser. In summary, we demonstrated two-photon interference from independent cavity-coupled dots on the same chip.…”
mentioning
confidence: 98%
“…This interference demonstrates that we attain sufficient tuning range and precision to match individual dots separated in distance by less than 15 m, a crucial requirement for scalable quantum photonics applications. These results represent an important step towards scalable quantum integrated photonic devices composed of multiple sources for photonic quantum information processing One of the main limitations to our indistinguishability contrast is that we used non-resonant above-band excitation which can cause decoherence and large time jitter in the emitted photons 40 .…”
mentioning
confidence: 99%
“…Investigating other filtering windows, we found that including only two more time bins brings us almost back to the unfiltered value of the coalescence probability. This postselection has the same effect as a temporal shaping of the QD photons, as presented in [16,23]. In the case of our quantum dot-SPDC HOM interference, the temporal filtering discards photons that do not overlap in time, on top of removing incoherent photons from the QD luminescence.…”
Section: Hom Interferencementioning
confidence: 94%
“…In [16], we reported the indistinguishability of photons consecutively emitted by a quantum dot. The result, plotted in figure 1(b), shows an indistinguishability contrast of 0.39 (2).…”
Section: Quantum Dot Characteristicsmentioning
confidence: 99%
“…Two-level QD transitions can generate single photons with a high degree of indistinguishability [1][2][3][4][5][6][7][8][9][10][11][12][13], an ideal resource for implementing future quantum photonic technologies such as boson sampling [14,15] and perhaps ultimately linear optical quantum computing. Multilevel QD systems, including the biexciton → exciton → ground−state cascade and so-called spin−λ systems [16,17] can be used to generate entangled photon pairs [18][19][20][21] and spin-photon entanglement [22][23][24], respectively, which can underpin implementations of quantum repeaters and networks [25].…”
Section: Introductionmentioning
confidence: 99%